PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PERUSAHAAN PERKEBUNAN KELAPA SAWIT (Kasus Bagian Pengolahan Pabrik Pada PT. Adei Plantation and Industry Pinggir - Bengkalis ) - Mubin, Al; Farida, Lena (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
High employee performance will have an impact on company performance. Employee performance is not a coincidence, but many factors influence among the supervision and motivation.This study aims to identify and analyze the implementation of the supervision of the oil palm plantation company leader in the processing factory of PT. Adei Plantation and Industry Pinggir-Bengkalis, to identify and analyze the motivation of employees of oil palm plantation companies in the processing factory of PT. Adei Plantation and Industry Pinggir - Bengkalis, to determine and analyze the performance of the company's employees in the oil palm processing factory of PT. Adei Plantation and Industry Pinggir - Bengkalis, to determine and analyze the effect on performance monitoring and motivation of employees in the processing factory of PT. Adei Plantation and Industry Pinggir - Bengkalis. This research is descriptive quantitative statistical calculations. The statistical analysis used in this research is multiple linear regression. The population in this study are employees of the processing plant as many as 78 people. The sample used in this study are taken entirely from the overall number of population.The results showed that the supervision of the leadership at the processing factory of PT. Adei Plantation and Industry Pinggir-Bengkalis in the category